Sunscreen Protection Against Visible Light: Is It Needed? - Dian Andriani Ratna Dewi (Universitas Malahayati Lampung, 2022)
ABSTRACT Ultraviolet radiation and Visible light (VL) have biological effects on the skin. VL causes erythema in light-skinned individuals and pigmentation in dark-skinned individuals. Broad-spectrum sunscreen protects skin against ultraviolet radiation but does not adequately protect against VL. The purpose of this study was to analyze the biological effects of visible light (VL) and the choice of sunscreen that can protect it. The research method used in this study is a qualitative descriptive method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data.The protection provided by organic (mineral) and inorganic sunscreen filters can prevent skin damage due to ultraviolet radiation, but does not provide protection against VL. Only tinted sunscreens that use formulations of concentrated iron oxide and titanium dioxide can provide protection against VL. Various steps have been taken to provide photoprotection against VL. There are many sunscreens available that combine percentages level of iron oxide and titanium dioxide pigment to suit all skin types. This tinted sunscreen is beneficial for melasma and post-inflammatory hyperpigmentation and photodermatosis induced by VL. Keywords: Iron Oxide, Photoprotection, Tinted Sunscreen, Titanium Dioxide, Ultraviolet Light, Visible Light